Impact of Left Ventricular Function and Heart Failure Symptoms on Outcomes Post Ablation of Atrial Fibrillation in Heart Failure: CASTLE-AF Trial. (October 2020) - Sohns, Christian; Zintl, Konstantin; Zhao, Yan; Dagher, Lilas; Andresen, Dietrich; Siebels, Jürgen; Wegscheider, Karl; Sehner, Susanne; Boersma, Lucas; Merkely, Béla; Pokushalov, Evgeny; Sanders, Prashanthan; et al.
Abstract : Background: Recent data demonstrate promising effects on left ventricular dysfunction and left ventricular ejection fraction (LVEF) improvement following ablation for atrial fibrillation (AF) in patients with heart failure. We sought to study the relationship between LVEF, New York Heart Association class on presentation, and the end points of mortality and heart failure admissions in the CASTLE-AF study (Catheter Ablation for Atrial Fibrillation With Heart Failure) population. Furthermore, predictors for LVEF improvement were examined. Methods: The CASTLE-AF patients with coexisting heart failure and AF (n=363) were randomized in a multicenter prospective controlled fashion to ablation (n=179) versus pharmacological therapy (n=184). Left ventricular function and New York Heart Association class were assessed at baseline (after randomization) and at each follow-up visit. Results: In the ablation arm, a significantly higher number of patients experienced an improvement in their LVEF to >35% at the end of the study (odds ratio, 2.17; P <0.001). Compared with the pharmacological therapy arm, both ablation patient groups with severe (<20%) or moderate/severe (≥20% and <35%) baseline LVEF had a significantly lower number of composite end points (hazard ratio [HR], 0.60; P =0.006), all-cause mortality (HR, 0.54; P =0.019), and cardiovascular hospitalizations (HR, 0.66; P =0.017). In the ablation group, New York Heart Association I/II patients at the time of treatment had the strongest improvement in clinical outcomes (primary end point: HR, 0.43; P <0.001; mortality: HR, 0.30; P =0.001). Conclusions: Compared with pharmacological treatment, AF ablation was associated with a significant improvement in LVEF, independent from the severity of left ventricular dysfunction. AF ablation should be performed at early stages of the patient's heart failure symptoms. Abstract : Supplemental Digital Content is available in the text.